Multiple autoimmune disease in a patient with hyperprolactinemia (2005)
The “mosaic of autoimmunity” describes the multifactorial origin and diversity of expression of autoimmune diseases. The term implies that different combinations of the many factors involved in autoimmunity produce varying and unique clinical pictures that represent the wide spectrum of autoimmune diseases. Most of the factors involved in autoimmunity can be categorized into four groups: genetic, immune defects, hormonal, and environmental.